Sales Promotion, Store Environment Dan Perceived Value Sebagai Prediktor Terhadap Purchase Decision - Valentine Pretty Lonita; Tommy Setiawan Ruslim (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This research was aimed to examine empirically sales promotion, store environment and perceived value as predictors of purchase decision of Hero Mall Ciputra consumers at the Faculty of Economics, Tarumanagara University. The sample of this study was the Tarumanagara University Faculty of Economics student. Tools for collection data using questionnaire. The number of respondents sample taken for research is 110 people. Data analysis method used is Multiple Linear Regression Analysis with a significance level of 0.05 and the t-test. The results of this reseacrh showed that sales promotion, store environment and perceived value have a significant effect to purchase decision.Penelitian ini bertujuan untuk menguji secara empiris sales promotion, store environment dan perceived value sebagai prediktor terhadap purchase decision konsumen Hero Mall Ciputra di Fakultas Ekonomi Universitas Tarumanagara. Sampel penelitian ini adalah mahasiswa/i Fakultas Ekonomi Universitas Tarumanagara. Alat untuk mengumpulkan data menggunakan kuesioner. Jumlah sampel di dalam penelitian ini sebanyak 110 orang. Metode analisis data yang digunakan adalah Analisis Regresi Linear Ganda dengan tingkat signifikansi sebesar 0,05, dan uji-t. Hasil penelitian ini menunjukkan bahwa sales promotion, store environment dan perceived value berpengaruh signifikan terhadap purchase decision.